2014
DOI: 10.1542/peds.2014-0899
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia and Neonatal Encephalopathy

Abstract: Data from large randomized clinical trials indicate that therapeutic hypothermia, using either selective head cooling or systemic cooling, is an effective therapy for neonatal encephalopathy. Infants selected for cooling must meet the criteria outlined in published clinical trials. The implementation of cooling needs to be performed at centers that have the capability to manage medically complex infants. Because the majority of infants who have neonatal encephalopathy are born at community hospitals, centers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 295 publications
(84 citation statements)
references
References 28 publications
0
84
0
Order By: Relevance
“…9,10 The American Academy of Pediatrics published a framework to ensure appropriate use of hypothermia. 11 …”
mentioning
confidence: 99%
“…9,10 The American Academy of Pediatrics published a framework to ensure appropriate use of hypothermia. 11 …”
mentioning
confidence: 99%
“…20 This study of whole-body hypothermia to an esophageal temperature of 32.0°C or continued for 120 hours was designed to evaluate potential benefit of longer cooling, deeper cooling, or both. The trial was closed to patient enrollment because of safety and futility concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Human clinical trials have shown that hypothermia is a relatively safe intervention [44]. In general, clinical trials have shown improvements in outcomes, such as mortality, seizure rate and neurological outcomes [6]. However, some reports have failed to definitively demonstrate improvements [45].…”
Section: Discussionmentioning
confidence: 99%
“…These deficits occur because the developing forebrain is very sensitive to hypoxic-ischemic injury (HI) [5]. Treatment options for neonatal HI are extremely limited, and hypothermia is the only widely used and well-validated therapy that is effective in reducing rates of permanent neurocognitive disability [6,7,8]. Since the fundamental pathophysiology of neonatal HI involves massive neuronal death [9], one promising pathway to substantial recovery is through repopulation of lost cells by enhancement of neural stem cell activity.…”
Section: Introductionmentioning
confidence: 99%